Coordinate Transformations in Object Recognition. [article]. - Graf, Makus
A basic problem of visual perception is how human beings recognize objects after spatial transformations. Three central classes of findings have to be accounted fro (a) Recognition performance varies systematically with orientation, size and position; (b) recognition latencies are sequentially additive, suggesting analogue transformation processes; and (c) orientation and size congruency effects indicate that recognition invloves the adjustment of a reference frame. All 3 classes of findings can be explained by a transformational framework of recognition : Recognition is achieved by an analogue transformation of a perpetual coordinate system that aligns memory and input representations. Coordinate transformation can be implemented neurocomputationally by gain (amplitude) modulation and may be regarded as a general processing principle of the visual cortex. -- (from the author)